Understanding Popular Education and Arts Based Learning Within Groups Through a Peace Workshop - Michelle Glowacki-Dudka; Amy Ward (Adult Education Research Conference, 2018)
Through the experience of a Peace Workshop and literature, the importance of both informal and arts-based learning during group events is necessary. Community and group norms provides strong cohesiveness.
Keywords: popular education; peace; participatory action research